EFFECT OF PELVIC FLOOR MUSCLE BIOFEEDBACK ON IMPROVED ERECTILE FUNCTION IN PATIENTS WITH LOWER URINARY TRACT SYMPTOMS: PRELIMINARY STUDY - Meilinda, Astrid; Purba, Herdiman Bernard; Birowo, Ponco; Kekalih, Aria (Indonesian Journal of Urology, 2025)
Objective: This study aims to determine the effect of giving pelvic floor muscle biofeedback on improving erectile function in patients with LUTS. Improvement in erectile function was assessed by IIEF (International Index of Erectile Function), EHS (Erectile Hardness Score), and pelvic floor muscle strength. Improvement in LUTS symptoms was assessed by an IPSS (International Index of Prostate Symptoms). Material & Methods: This research was a randomized controlled trial study on outpatients at Cipto Mangunkusumo General Hospital. The research subjects were divided into 2 groups, the treatment group received 10 sessions of pelvic floor muscle biofeedback and home exercise. The control group only received home exercise. Results: There were 21 LUTS patients with ED. A total of 10 subjects (50%) had mild ED, 4 subjects (20%) had moderate ED, and 6 subjects (30%) had severe ED. From the results of the study, it was found that the scores for IIEF, IPSS, EHS, slow twitch, and fast twitch were improved in the treatment group (p-value <0.05), whereas in the control group there were only improvements in IIEF and IPSS scores (p-value <0.05). Conclusion: There was an improvement in erectile function (increased IIEF score, EHS score, decreased IPSS score, and increased pelvic floor muscle strength) after pelvic floor muscle biofeedback in ED patients with LUTS for 10 sessions. Keywords: Biofeedback, erectile dysfunction, pelvic floor muscle exercises, lower urinary tract symptoms (LUTS).